Language Policy: European Criteria and Ukraine - Azhniuk, Bohdan (Ukrainian linguistics, 2019)
The article discusses a much debated in Ukraine issue: what are the principles of language policy that can be labelled European, what are the major sources for the deduction of these principles and to what extant they could be implemented in Ukraine’s current language policy. It is argued that these principles can be deduced from the following major sources: national constitutions and legislative acts on language issues, international legal instruments (The European Charter of regional or Minority Languages), international declarations (The Universal Declaration of Linguistic Rights) that are not legal instruments at the moment, expert opinions of international committees and other bodies like the Venice Commission, OSCE, etc, scientific publications on language policy and language planning. The analysis of these sources gives justification to the following principles as reflecting the mainstream European conception of language policy and language planning: 1) maintaining the leading role of the official state language as the backbone of national unity, 2) protection of endangered languages and preservation of language diversity, 3) promotion of the bilingualism with sufficient competence in the state language, 4) effective management of the enforcement mechanism. The ratification by Ukraine of the European Charter for Regional or Minority Languages called attention to its implementation in Ukraine. The comparison of Ukraine with most European countries shows that in terms of linguistic rights the country’s main language (Ukrainian) is in a rather underprivileged position. There is growing awareness in the society that the idea of official or semi- official Ukrainian-Russian bilingualism was designed as an instrument of Russian foreign policy and became one of the key factors that provoked political instability in the country. Nowadays Russian is associated with the annexation of Crimea and justification of further aggression and the official upgrading of its status is perceived as a jeopardy for the Ukrainian national identity and statehood. The change of the popular attitude to the idea of the official bilingualism has modified the positions of the major political players. Information about the author: Bohdan Azhniuk – Dr Hab, Prof., Oleksandr Potebnia Institute of Linguistics, NAS of Ukraine (Ukraine). E-mail: azhniuk@gmail.com __________ References • Azhniuk B.M. (2013) Suchasni tendentsii v rozvytku slovianskoi sotsiolinhvistychnoi terminolohii (status mov) [Modern tendencies in the development of Slavic sociolinguistic terminology (language status)]. Movoznavstvo [Linguistics], no 2-3, pp. 163-183 (in Ukrainian). • Bowring B. (2008) Movna polityka v Ukraini. Mizhnarodni normy ta zoboviazannia i ukrainskyi zakon ta zakonodavstvo [Language policy in Ukraine. International norms and obligations and Ukrainian law and legislation]. Language policy and language situation in Ukraine. Kyiv: Kyiv-Mohyla аcad., рр. 55-95 (in Ukrainian). • Besters-Dilger Ju. (2010) Sylni ta slabki storony Yevropeiskoi khartii rehionalnykh abo minorytarnykh mov: zakhidnoievropeiskyi dosvid [Strong and weak points of the European Charter of Regional and Minority Languages: West-European experience]. Movoznavstvo [Linguistics], no 1, pp. 94-99 (in Ukrainian). • Bolman I. (2007) Movni viiny v Yevropi [Language wars in Europe. Transl. into Ukrainian from French]. Kyiv: K.I.S., 280 p. (in Ukrainian). • Brytsyn V.M. (2007) Movna polityka [Language policy]. Ukrainian language. Encyclopedia. Kyiv: Ukrainian еncyclopedia, рp. 375-378 (in Ukrainian). • Kresina I.O., Yavir V.A. (2008) Problema implementatsii norm mizhnarodnoho prava u natsionalne zakonodavstvo pro movy [The problem of implementation of the norms of international law into the national legislation language on language policy]. Language situation in Ukraine: Between conflict and consensus. Kyiv: IPiEND im. I.F.Kurasa NAN Ukrainy, pp. 190-204 (in Ukrainian). • Azhniuk B.M. (ed.) (2012) Ekolohiia movy i movna polityka v suchasnomu suspilstvi: zb. nauk. prats [Ecology of language and language polity in the contemporary society]. Kyiv: dim D.Buraho, 376 p. (in Ukrainian). • Mihalchenko V.Yu. (ed.) (2006) Slovar sotsiolingvisticheskih terminov [The dictionary of Sociolinguistic terms]. Moscow, 312 p. (in Russiаn). • Cherednychenko O.I. (2013) Zakhyst ofitsiinoi movy v natsionalnii derzhavi: dosvid Frantsii [Protection of the official language in the national state: The case of France]. Movoznavstvo [Linguistics], no 5, pp. 32-34 (in Ukrainian). • Arzoz X. (2008) The implementation of the Charter in Spain. The European Charter for Regional Or Minority Languages: Legal Challenges and Opportunities. Strasbourg, рр. 83-107. • Bastardas Boada A. (2002) World Language Policy in the Era of Glob-alization: Diversity and Intercommunication from the Perspective of ‘Complexity’. Revista de Sociolinguistica. Teoria i metodologia, Barcelona, рр. 1-9. • Besters-Dilger J. (2007) The Ukrainian Language in Education and Mass Media. Harvard Ukrainian Studies. Ukrainian Philology and Linguistics in the Twenty-First Century, vol. 29, no 1-4, рр. 257-293. • Fairless T. (2014) European Court Strikes Down German Language Test for Turks. The Wall Street Journ. URL : http://blogs.wsj.com/law /2014/07/10/european-court-strikes-down-german-language-test-for-turks. • Fishman J. (1974) Language modernization and planning in comparison with other types of national modernization and planning. Advances in Language Planning. The Hague: Mouton, рр. 79-102. • Grin F. (1998) Language policy developments in Switzerland: needs, opportunities and priorities for the next few years. Revue suisse de science politique, nо 3, рр. 108-113. • Hartig M. (1985) The Language Situation and Language Policy in Belgium. Language Policy and National Unity. Totowa, NJ, рр. 67-78. • Judge A. (2007) Linguistic Policies and the Survival of Regional Languages in France and Britain. Basingstoke; New York, рр. 129-136. • Phillipson R. (1999) International Languages and International Human Rights. Language: A Right and a Resource: Approaching Linguistic Human Rights. Budapest : Central European University Press, рр. 25-46. • Ricento T. (2007) Models and approaches in language policy and planning. Handbook of Language and Communication: Diversity and Change. The Hague: Mouton de Gruyter, рр. 211-240. • Schmitt N. (2017) Linguistic Policy in Switzerland: the Paradigm Shifts but the Complexity Remains. Revista de Llengua i Dret, Journal of Language and Law, no 67, рр. 86-105. • Skutnabb-Kangas T. (2003) Linguistic Diversity and Biodiversity. The Threat from Killer languages. The Politics of English as a World Language: New Horizons in Post-colonial Cultural Studies. Amsterdam; New York, рр. 31-52. • Van Parijs P. (2007) Linguistic diversity as curse and as by-product. Respecting Linguistic Diversity in the European Union. Amsterdam, рр. 17-46. • Van Parijs P. (2011) Linguistic Justice for Europe and for the World. Oxford, 320 р. • Williams G. (2005) Sustaining Language Diversity in Europe. Evidence from the Euromosaic Project. Basingstoke; New York, 251 р.